Optimisation of composite shapes with the help of genetic algorithms - Hufenbach, Werner; Gude, Maik; Kroll, Lothar; Kostka, Paweł; Sokołowski, Andrzej (Computer Assisted Methods in Engineering and Science, 2005)
During the manufacturing process of multilayered fibre-reinforced composites with variable fibre orientations, residual stresses build up due to the directional expansion of the single unidirectionally reinforced layers. Dependent on the laminate lay-up, these inhomogeneous residual stresses, which are caused by thermal effects, moisture absorption and chemical shrinkage, can lead to large multistable out-of-plane deformations. Instead of avoiding these laminate's curvatures, they can be advantageously used for technical applications following the near-net-shape technology. However, due to the effect that the laminate curvature depends on huge amount of different parameters such as anisotropic, hygroscopic and thermomechanical material properties, fibre orientations and ply thickness of each single layer as well as technological processing parameters, a search in a multi-dimensional search area is necessary. In order to solve such a task, Genetic Algorithms in combination with a fitness function based on a nonlinear semi-analytical calculation model for the laminate shape prediction have been applied and described in the paper. Using this approach, one can purposefully adapt the laminate lay-up dependent on the loading and process parameters.